2009
DOI: 10.1007/s10584-009-9739-3
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling extreme month-long anomalies in southern South America

Abstract: We investigate the performance of one stretched-grid atmospheric global model, five different regional climate models and a statistical downscaling technique in simulating 3 months (January 1971, November 1986, July 1996 characterized by anomalous climate conditions in the southern La Plata Basin. Models were driven by reanalysis (ERA-40). The analysis has emphasized on the simulation of the precipitation over land and has provided a quantification of the biases of and scatter between the different regional si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 49 publications
(32 reference statements)
0
31
0
3
Order By: Relevance
“…As in e.g. Carril et al (2012) and Menéndez et al (2010a), combining models in a multimodel ensemble gives a better climate description than any individual model, independently of the variable and the season. The regional models capture better the spatial characteristics of TN than those of TX: the spread between models is large for TX, with PROMES being the outlier model in this case.…”
Section: Seasonal Mean Fields Of Minimum and Maximum Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…As in e.g. Carril et al (2012) and Menéndez et al (2010a), combining models in a multimodel ensemble gives a better climate description than any individual model, independently of the variable and the season. The regional models capture better the spatial characteristics of TN than those of TX: the spread between models is large for TX, with PROMES being the outlier model in this case.…”
Section: Seasonal Mean Fields Of Minimum and Maximum Temperaturementioning
confidence: 99%
“…As SA is considered as a climate-data-sparse region (Menéndez et al 2010a, Tencer et al 2011, Rusticucci 2012, Skansi et al 2013, RCMs could represent a useful tool for the climatological study of extreme events. The ensemble of RCMs over this region has been shown to be a very interesting tool for these studies (Menéndez et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…To systematically explore uncertainties associated with dynamical downscaling, coordinated RCM simulations are necessary. Such coordinated efforts are available in other regions, such as Europe (e.g., Christensen and Christensen 2007), North America (Mearns et al 2009), and South America (Men endez et al 2010). CORDEX is the first effort to that focuses on the whole of Africa and furthermore treats it as a priority domain (Giorgi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the modelling of the current climate and the evaluation of projections of the effects of climate change on the basin, several studies were conducted by assembling different emission scenarios (RCP 8.5, RCP 6.0, RCP 4.5, and RCP 2.6) with regional climate models (RCM, e.g., REGCM3, RegCM4, Eta, RCA, MM5, and REMO) driven by global climate models (GCM, e.g., HadGEM2, HadCM3, MIROC5, EC5OM, ECHAM5, GFDL, and MPI) (e.g., [3,11,13,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]). In order to assess a wide range of uncertainty sources, in recent years many studies have followed an ensemble modelling approach.…”
Section: Introductionmentioning
confidence: 99%
“…The most ambitious collaborative initiative for producing ensembles of RCM simulations over the La Plata Basin was performed within the CLARIS-LPB Project (a Europe-South America network for climate change assessment and impact studies [42,43]). A suite of seven coordinated RCM simulations over South America (with an approximate grid resolution of 50 km) driven by both the ERA-interim [44] reanalysis and a set of GCMs were evaluated [34,[36][37][38][39][40]42]. Carril et al [36] found relatively good agreement for the annual precipitation average cycle over the La Plata Basin by applying an ensemble of RCMs.…”
Section: Introductionmentioning
confidence: 99%